APLIKASI METODE MATERIAL REQUIREMENT PLANNING DALAM PENGENDALIAN BIAYA PERSEDIAAN BAHAN BAKU PADA UMKM ANTI GALAU DI BOYOLALI - Erni Widajanti (ITB AAS Indonesia Surakarta, 2024)
The purpose of this study is to analyze the efficiency of raw material inventory costs at UMKM Anti Galau in Boyolali and to analyze whether the material requirement planning (MRP) method can make raw material inventory costs more efficient. The location of this study is a home business called UMKM Anti Galau in Boyolali which produces various fried dumplings. The main raw materials for fried dumplings are wheat flour, cooking oil and butter.The data analysis method in this study uses the Material Requirement Planning method with the Lot For Lot (LFL), Economic Order Quantity (EOQ) and Periodic Order Quantity (POQ) techniques. The results of the study showed that the total inventory cost according to the Anti Galau UMKM owner's policy was IDR 851,495, - with the LFL method of IDR 603,280, - with the EOQ method of IDR 216,122.84, - and with the POQ method of IDR 648,370.56, - The results of the calculation of the level of cost efficiency, the MRP method (LFL, EOQ and POQ) are more efficient than the calculation of raw material inventory costs according to the Anti Galau UMKM owner's policy. Cost savings with the LFL method are 29.15%, with the EOQ method will save costs by 74.62% and with the POQ method will save costs by 23.86%. From the results of the analysis, all hypotheses in this study are proven true. Keywords: Material Requirement Planning